Improving Mental Health of Children and Adolescent Through Islamic Worship - Triana Srisantyorini; Ernyasih Ernyasih; Nur Romdhona; Noor Latifah (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2022)
From the development of the current era, it has a positive and negative impact on the stages of development of children and adolescents. Among them are moral development and mental health for adolescents as individuals in the category of child development in the final phase. The results of previous studies concluded that adolescents need self-control guidelines for thinking and acting, in this case Islam. To develop the health potential of children and adolescents, especially for the mental health of adolescents, it can be done by channeling the potential for creativity in writing, music and art as well as other good works. And because of that, with the great potential of adolescent, ideas should be developed for the development of adolescent mental health according to Psychology and Islam through Islamic worship so that the life goals of adolescents as students become focused. This scientific article uses research methods from the library. From the results of literature research, it is shown that children and adolescents who understand and live worship, increase their sense of gratitude, are able to adapt to the environment, maintain relationships with the environment and God, are able to overcome problems in their lives.